2006
DOI: 10.1124/jpet.106.114835
|View full text |Cite
|
Sign up to set email alerts
|

Role of 90-kDa Heat Shock Protein (Hsp 90) and Protein Degradation in Regulating Neuronal Levels of G Protein-Coupled Receptor Kinase 3

Abstract: Cellular levels of G protein-coupled receptor kinase (GRK)3 determine the sensitivity of the ␣ 2A/B -adrenoceptor (␣ 2 -AR) to agonist-induced down-regulation. Using human neuroblastoma BE(2)-C cells, this study examines how cellular GRK3 levels are affected by several mechanisms reported to influence stability and degradation of other GRKs. We first examined the interaction between the 90-kDa heat shock protein (Hsp90) and GRK3; Hsp90 reportedly affects the maturation and stability of GRK2. In unstimulated ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
(43 reference statements)
2
13
0
Order By: Relevance
“…Results from test Western blots gave a prominent band at the predicted molecular weight for each isoform based on antibody data sheets. Representative bands from our Western blots are consistent with previous reports from the literature (Ahmed et al, 2008a; Bezard et al, 2005; Bychkov et al, 2011a; Bychkov et al, 2012; Bychkov et al, 2011c; Bychkov et al, 2008a; Ertley et al, 2007; Salim and Eikenburg, 2007; Zhang et al, 2014). …”
Section: 1 Experimental/materials and Methodssupporting
confidence: 91%
“…Results from test Western blots gave a prominent band at the predicted molecular weight for each isoform based on antibody data sheets. Representative bands from our Western blots are consistent with previous reports from the literature (Ahmed et al, 2008a; Bezard et al, 2005; Bychkov et al, 2011a; Bychkov et al, 2012; Bychkov et al, 2011c; Bychkov et al, 2008a; Ertley et al, 2007; Salim and Eikenburg, 2007; Zhang et al, 2014). …”
Section: 1 Experimental/materials and Methodssupporting
confidence: 91%
“…Chaperone association of CXCR4 with hsp90 in AML cells was further confirmed by the observation that treatment with AUY922 also disrupted the binding of CXCR4 to hsp90 and depleted CXCR4 levels. Consistent with the previous report that GRKs, including GRK3, are also chaperoned by hsp90, 43,44 findings presented here demonstrate that PS and AUY922 treatment also depletes GRK3 levels and inhibits GRK3 binding to hsp90 in AML cells. In addition, treatment with PS also lowered the levels of other signaling hsp90 client oncoproteins in AML cells, including AKT and c-RAF, which are activated by CXCL12 binding and activation of CXCR4.…”
Section: Discussionsupporting
confidence: 81%
“…Zou et al (1998) have shown that GA also disrupts a complex consisting of Hsp90 and the heat shock transcription factor HSF1 and triggers the activation of a heat shock response in mammalian cells. Low GA treatment might therefore have a binary function, one to elevate the level of Hsp90 similar to preconditioning by the heat shock response mentioned above, and the other to block the binding of substrates with the association of Hsp90 which may result in reducing the degradation of stress-induced misfolded proteins (Salim and Eikenburg 2007;Young et al 2004).…”
Section: Discussionmentioning
confidence: 99%